2009
DOI: 10.1029/2007wr006526
|View full text |Cite
|
Sign up to set email alerts
|

Implications of anthropogenic river stage fluctuations on mass transport in a valley fill aquifer

Abstract: [1] In humid regions a strong coupling between surface water features and groundwater systems may exist. In these environments the exchange of water and solute depends primarily on the hydraulic gradient between the reservoirs. We hypothesize that daily changes in river stage associated with anthropogenic water releases (such as those from a hydroelectric dam) cause anomalous mixing in the near-stream environment by creating large hydraulic head gradients between the stream and adjacent aquifer. We present fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 29 publications
2
39
0
Order By: Relevance
“…Therefore, frequent, short‐term stream fluctuations will be more efficient than flow event of longer duration with lower peaks in mobilization and consequent export of solutes into the stream. Boutt and Fleming () also demonstrated that frequent stream fluctuations transport solute mass from the stream to the aquifer under zero net water flux by enhancing mixing process inside the aquifer. Gu et al () found that strong stream events significantly influence the chemistry of both surface water and groundwater by enhancing mixing and reaction efficiency in the near stream zone.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, frequent, short‐term stream fluctuations will be more efficient than flow event of longer duration with lower peaks in mobilization and consequent export of solutes into the stream. Boutt and Fleming () also demonstrated that frequent stream fluctuations transport solute mass from the stream to the aquifer under zero net water flux by enhancing mixing process inside the aquifer. Gu et al () found that strong stream events significantly influence the chemistry of both surface water and groundwater by enhancing mixing and reaction efficiency in the near stream zone.…”
Section: Resultsmentioning
confidence: 98%
“…Numerical simulations have been used to examine the effect of tidal fluctuation on the spreading of a solute plume (Zawadzki et al 2002;Elfeki et al 2007;Robinson et al 2007;Boutt and Fleming 2009). Yim and Mohsen (1992) showed mathematically that tidal fluctuations cause the concentration levels discharging to coastal waters to be lowered due to dilution.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies presented direct hydraulic observations of hyporheic flows in regulated river systems (Arntzen et al 2006;Boutt and Fleming 2009;Fritz and Arntzen 2007;Gerecht et al 2011;Sawyer et al 2009), and geophysical observations revealed the extent to which these exchanges may occur (Cardenas and Markowski 2011;Johnson et al 2012). Some studies have focused on processes occurring within the streambed (Arntzen et al 2006), while others emphasized processes within the banks (Boutt and Fleming 2009;Gerecht et al 2011).…”
Section: Introduction and Objectivesmentioning
confidence: 95%
“…This may promote additional denitrification in the bank sediment, though this increase is relatively small compared to denitrification in the riverbed (Gu et al 2012). Still, some modeling studies showed that because of dispersion, conservative solutes that enter the banks during repeated flood pulses may linger well beyond the flood duration (Boutt and Fleming 2009;McCallum et al 2010), potentially providing opportunities for a host of biogeochemical reactions to occur.…”
Section: Introduction and Objectivesmentioning
confidence: 99%